Strategi Bisnis Usaha Mikro Kecil Melalui Analisis SWOT Pada Usaha Dagang Di Desa Sari Mekar (Studi Kasus UD Toya Mertaada) - I Ketut Suardika; Gede Ardana Yasa (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
The industrial revolution makes a person have to think critically and creatively with implementation through entrepreneurship, namely in the form of micro, small and medium enterprises which until now have become one of the potential and promising business opportunities. Development of micro, small and medium enterprises will increase business competition, such as UD Toya Mertaada, which is located in Sari Mekar Village, must implement a business strategy so that the business being run has a competitive advantage. This type of research is a qualitative research that seeks to collect facts and circumstances properly through interviews. The interview technique used is an unstructured interview which freely asks various questions to the informant. Interviews were conducted with business owners, employees, and several consumers. The results obtained based on the SWOT analysis show that UD Toya Mertaada is in Quadrant I. This indicates that UD Toya Mertaada has great opportunities and strengths so that they can take advantage of existing opportunities. It can be concluded that the strategy implemented is to support an aggressive growth policy (Growth Oriented Strategy), with the implementation of this strategy UD Toya Mertaada can maximize its strengths to take the opportunities that exist so that it can compete with other businesses, and it is even possible to win the business competition.